2016
DOI: 10.3390/nu8020100
|View full text |Cite
|
Sign up to set email alerts
|

Allomyrina Dichotoma Larvae Regulate Food Intake and Body Weight in High Fat Diet-Induced Obese Mice Through mTOR and Mapk Signaling Pathways

Abstract: Recent evidence has suggested that the Korean horn beetle (Allomyrina dichotoma) has anti-hepatofibrotic, anti-neoplastic, and antibiotic effects and is recognized as a traditional medicine. In our previous works, Allomyrina dichotoma larvae (ADL) inhibited differentiation of adipocytes both in vitro and in vivo. However, the anorexigenic and endoplasmic reticulum(ER) stress-reducing effects of ADL in obesity has not been examined. In this study, we investigated the anorexigenic and ER stress-reducing effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 47 publications
0
41
0
1
Order By: Relevance
“…Moreover, the PI3K-Akt, AMPK, and mTOR signaling pathways, which were correlated with fat synthesis and metabolism, were significantly enriched by KEGG analysis. 50,51 The data above preliminarily suggest that melatonin decreased cellular TAG levels via the PI3K-Akt, mTOR, and AMPK signaling pathways during milk fat synthesis in BMECs. mTOR links with other proteins and serves as a core component of two distinct protein complexes, mTORC1 and mTORC2, which regulate different cellular processes and play significant roles in milk fat synthesis as the vitally important signaling pathway.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Moreover, the PI3K-Akt, AMPK, and mTOR signaling pathways, which were correlated with fat synthesis and metabolism, were significantly enriched by KEGG analysis. 50,51 The data above preliminarily suggest that melatonin decreased cellular TAG levels via the PI3K-Akt, mTOR, and AMPK signaling pathways during milk fat synthesis in BMECs. mTOR links with other proteins and serves as a core component of two distinct protein complexes, mTORC1 and mTORC2, which regulate different cellular processes and play significant roles in milk fat synthesis as the vitally important signaling pathway.…”
Section: Discussionmentioning
confidence: 90%
“…To elucidate the specific effects of melatonin on TAG level in BMECs, we investigated the expression profiles of core metabolic genes in BMECs and found that melatonin decreased the expression of lipid metabolism–related genes, including PPARγ , FASN , and SCD . Moreover, the PI3K‐Akt, AMPK, and mTOR signaling pathways, which were correlated with fat synthesis and metabolism, were significantly enriched by KEGG analysis . The data above preliminarily suggest that melatonin decreased cellular TAG levels via the PI3K‐Akt, mTOR, and AMPK signaling pathways during milk fat synthesis in BMECs.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, ADL inhibited the differentiation of adipocytes through the downregulation of adipogenic or lipogenic transcription factors [11,22]. In addition, central administration of an ethanol extract of ADL reduced food intake and body weight through the regulation of appetite-related neuropeptides in high-fat diet (HFD)-fed mice [23]. In our previous study, we investigated the nutrient profiles of Tenebrio molitor larvae (TML) [33].…”
Section: Discussionmentioning
confidence: 99%
“…In our previous work, we reported that oral administration of another insect, Allomyrinal dichotoma , inhibits the differentiation of adipocytes in vitro and in vivo [11,22]. Furthermore, intracerebroventriular (ICV) administration of an ethanol extract of Allomyrinal dichotoma larvae (ADL) reduces food intake and body weight via the regulation of appetite-related neuropeptides including neuropeptide Y (NPY), agouti-related protein (AgRP), and α-melanocyte-stimulating hormone (α-MSH) in high-fat diet (HFD)-fed mice [23]. …”
Section: Introductionmentioning
confidence: 99%
“…The Korean horn beetle, Allomyrina dichotoma (Linné 1771) is one of the major insects whose larvae have been consumed as traditional oriental medicine for liver disease and diabetes for a long time. Moreover, it has been reported that extracts from A. dichotoma larvae offer various biological benefits such as antibacterial (Niu et al 2016;Koyama et al 2006;Sagisaka et al 2001), anti-Alzheimer's disease (Kim et al 2014), anti-obesity (Kim et al 2016;Yoon et al 2015;Chung et al 2014), and antioxidant effects (Suh et al 2010).…”
Section: Introductionmentioning
confidence: 99%